Análise dos indicadores de sustentabilidade da agricultura familiar participante do PNAE no município de Pato Bragado – PR - Daniel , Daniela Silveira (2022)
Family farming is the main source of food in the world, in addition to being a source of sustainable rural development, it remains closely linked to public policies, such as the National School Feeding Program (PNAE), in which families can obtain a Extra income, producing in rural areas. The objective of the present study was to evaluate the sustainability indicators of family farming properties participating in the National School Feeding Program (PNAE), in the municipality of Pato Bragado - PR, using the Sustainable Rural Development Assessment Methodology, MADERUS, developed by Hein, 2019. The research was carried out in 2021 in seven rural properties, using a quali-quantitative approach, applied to the field, being an exploratory and descriptive research, in order to observe, record and analyze the properties in question. The data were collected through semi-structured interviews and were later tabulated and systematized through the proposed methodology, resulting in the Sustainable Rural Development Index - IDRS, which can be observed clearly and objectively through the radar chart and the composite indicators chart. As a result, it was found that the IDRS of the properties varied between 7.49 and 9.13, on a scale from 0 to 10. They proved to be sustainable according to the MADERUS methodology, needing only a few punctual adjustments to raise the sustainability. As observed in the joint analysis of composite indicators, the most critical points are related to health, continuity and succession indicators, as well as financial management. The most expressive positive indicators are in managerial autonomy and compliance with legislation. Furthermore, it can be proved that the MADERUS methodology is efficient and adequate to determine the level of sustainability of rural properties.